METHODS OF SPEECH DEVELOPMENT (Scientific journal of the Fergana State University, 2025)
Methods of speech development include various approaches and are used in all age groups in the educational system. This article provides detailed information about the main methods of speech development, its pedagogical essence, methodological recommendations and practical application.